1986
DOI: 10.1002/1098-2337(1986)12:1<57::aid-ab2480120108>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and the nonlegal equivalent of aggressive criminal behavior

Abstract: Within the framework of modern evolutionary theory, arguments are reviewed that the nonlegal equivalent of aggressive criminal behavior may have evolved by natural selection among mammals, particularly primates, as part of their overall approach to reproduction. If so, the commission of aggressive crimes (or their nonlegal equivalent) by humans, and even efforts to prevent fellow social group members from being victimized by aggressive crimes, may also be partially explainable in natural selection terms. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These measures ensure the continuity of the sanctioning and re-education process that began with the application of a classic punishment. The studies carried out (Ellis, 1986) concluded that 78% of criminals consider intermediate sanctions to be more difficult to execute than classic ones and, therefore, harsher, because they force them to adopt a completely different behavior than they had before committing the crime and forces them to reshape their perception and way of thinking about life, but at the same time they considers these measures to be welcome, because they avoid the prison sentence, which is by far viewed with the greatest hostility (Spelman, 1995, p. 107).…”
Section: The Liberal Model Of Criminal Repression -Criminal Technique...mentioning
confidence: 99%
“…These measures ensure the continuity of the sanctioning and re-education process that began with the application of a classic punishment. The studies carried out (Ellis, 1986) concluded that 78% of criminals consider intermediate sanctions to be more difficult to execute than classic ones and, therefore, harsher, because they force them to adopt a completely different behavior than they had before committing the crime and forces them to reshape their perception and way of thinking about life, but at the same time they considers these measures to be welcome, because they avoid the prison sentence, which is by far viewed with the greatest hostility (Spelman, 1995, p. 107).…”
Section: The Liberal Model Of Criminal Repression -Criminal Technique...mentioning
confidence: 99%
“…Research has clearly shown that males are more likely to be the perpetrator in rape cases compared to females. Similarly, rape (i.e., forced copulation) is not a human-specific behavior; it occurs in many other species, especially in those who are genetically similar to humans, such as orangutans (Ellis 1986). In 2000, Thornhill and Palmer presented an evolutionary explanation of rape in their book A Natural History of Rape: Biological Bases of Sexual Coercion.…”
Section: Rapementioning
confidence: 99%
“…In addition, criminality can be conceptualized as the opposite of altruism, traditionally having been viewed as causing social harm and a disruption to society (Rushton, 1980). One analysis of the evolution of "rulefollowing" behaviour was provided by Ellis (1986) who demonstrated their non-legal equivalents, and compensatory policing strategies, in nonhuman primates. Of crucial importance is the subsequent work of Ellis (1987Ellis ( , 1989 directly applying r-K theory to crime including rape, with forced copulation conceptualized as an rreproductive strategy because it emphasizes mating rather than parenting effort.…”
Section: Is Rushton's Application Of R-k Theory Incorrect?mentioning
confidence: 99%